Iceland in the UNHRC 2018-2019: Power potential of small states in the global community - Vala Bjarney Gunnarsdóttir 1990- (2021)
In June 2018 the United States suddenly resigned from the United Nations Human Rights Council. The spotlight quickly turned to Iceland to take its place. After an exceptionally short campaign, Iceland won the election and became the smallest state ever to hold membership status in the Human Rights Council. The aim of this thesis is to analyze how small state theories and constructivism explain the power potential of small states in international organizations such as the Human Rights Council. In that context, Iceland’s participation in the Human Rights Council will be examined, as well as how Iceland’s identity has changed from being an ineffective actor in the global community to being an active participant. Three interviews were conducted with representatives of the Icelandic foreign service, with the goal of achieving deeper knowledge of the subject. The main results of this study are that Iceland certainly did behave in many ways like a typical small country in international cooperation. However, there are some deviations, such as Iceland’s initiative in a resolution on the human rights situation in the Philippines. Í júní mánuði árið 2018 bauðst tækifæri til að bjóða sig fram sem fulltrúi vestrænna landa í mannréttindaráði Sameinuðu þjóðanna þegar Bandaríkin sögðu sig óvænt úr ráðinu þegar einungis helmingur af tímabili þeirra sem meðlimur var liðinn. Ísland bauð sig fram og hlaut kosningu tveimur vikum ríflega eftir að spjótin beindust fyrst að því sem mögulegur kandídat. Við tóku 18 mánuðir af mikilli vinnu utanríkisþjónustunnar. Markmið þessarar ritgerðar er að gera grein fyrir hvernig kenningar í smáríkjafræði og mótunarhyggja (en. constructivism) útskýra möguleika smáríkja til að hafa áhrif innan alþjóðastofnana líkt og mannréttindaráðsins. Í því ljósi verður litið til starfa Íslands í mannréttindaráðinu, sem og að skoða hvernig ímynd (en. identity) Íslands sem smáríki hefur breyst úr því að vera áhrifalaus viðtakandi í alþjóðlegu samhengi til þess að vera virkur þátttakandi. Tekin voru viðtöl við ...